R. V. Cuhna. Will I ever be a Cyborg? / trans. from Engl. R. L. Kochnev - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
Eric Olson’s animalist view relies on the premise that person is not a fit candidate to be a substance concept, in Wiggins’s terminology. Instead, he claims, animal is what best serves as the answer to what we most fundamentally are and what determines our persistence conditions. Pro-posing a thought experiment concerning inorganic replacement, I aim to show that Olson’s animalist view cannot accommodate our very strong intuitions about such cases. My claim is then that animalism either fails on its own grounds or requires some tuning regarding what exactly an organism is and its persistence conditions. I will examine Matthew Liao’s attempt to accommodate such intuitions within an animalist view. I will also describe the basics about Olson’s animalist view but let us first look at the rough outline of my thought experiment. The essentials are as follows, the rest I will provide later, as we go along.